Evaluation of immune correlates to TB vaccines - Marsay, L (2011)
Development of an improved TB vaccine is hindered by the lack of a correlate of protection. Efficacy of TB vaccines in humans can only be assessed by expensive and time consuming trials within TB endemic areas, which are limited; therefore, it is critical that vaccines with the greatest potential to protect are selected for these trials. Mycobacterial growth inhibition assays (MGIAs) have been developed with the hope that these in vitro functional assays will correlate with protection, which could aid in the selection of the best vaccine candidates. Work in this thesis describes the development and evaluation of different MGIAs for their ability to detect TB vaccine induced mycobacterial growth inhibition. The mycobacterial growth indicator tube (MGIT) MGIA reproducibly demonstrated mycobacterial growth inhibition in splenocytes from BCG vaccinated compared with naïve mice, which corresponded with in vivo protection from M. tb challenge. This assay also discriminated between PBMC from naïve and BCG/BCG-MVA85A vaccinated macaques. Microarray data showed extensive differential gene expression in splenocyte responses to ex-vivo BCG stimulation between naïve and BCG vaccinated mice. TH1 responses including IFN- with NOS2 expression were enhanced in BCG vaccinated mice, indicating a possible mechanism for mycobacterial growth inhibition in BCG vaccinated mice. Further investigation into whether the MGIT assay can be used as a correlate of protection from M. tb in humans and animals is warranted.